THE EFFECTIVENESS OF PEER COUNSELING IN THE PREVENTION OF SENIOR BULLYING AGAINST STUDENTS IN THE DORMITORY: A LITERATURE REVIEW - Elis Ela Susila (COMPASS: Journal of Education and Counselling, 2025)
Seniority bullying in the dormitory environment is a phenomenon that still occurs frequently and has a negative impact on students' mental health, social development, and academic achievement. One of the prevention strategies that is starting to get attention is peer counseling, which is a peer counseling service that involves students as counselors to help their peers. This article aims to review various previous studies on the effectiveness of peer counseling in preventing seniority bullying. The research method used is literature review by examining 15 relevant international and national articles in the range of 2015–2024. The results of the study showed that peer counseling was effective in increasing anti-bullying awareness, strengthening assertive communication skills, and building a supportive social environment in the dormitory. However, its effectiveness is influenced by the quality of peer counselor training, the support of educational institutions, and the involvement of teachers and dormitory coaches. These findings confirm the importance of implementing peer counseling as a preventive strategy for seniority bullying, noting the need for professional supervision and ongoing evaluation. This research is expected to be a reference for schools and dormitories in designing evidence-based peer counseling.